Comparison of KAtex, Bone Marrow Aspiration and DAT for the Diagnosis of Visceral Leishmaniasis (Bangladesh Journal of Infectious Diseases, 2019)
Background: Newly developed KAtex test can be used as a non invasive tool for diagnosis of Kala-azar.Objectives: The aim of the present study was to compare KAtex, Bone marrow aspiration and DAT to diagnose VL.Methodology: This cross-sectional study was carried out in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh in collaboration with the Department of Parasitology, Institute of Epidemiology, Disease Control and Research (IEDCR), Dhaka, Bangladesh for a period of one year. Clinically suspected Kala-azar (VL) cases of different age and sex attending IEDCR, Dhaka from different Kala-azar endemic areas of Bangladesh were selected for this study. Patients having fever for more than 2 weeks, with or without splenomegaly, having history of loss of body weight following onset of fever were clinically suspected as Kala-azar cases. Microscopy and culture was performed in bone marrow (BM). KAtex was performed with urine sample. Agglutination of sensitized latex indicated presence of Leishmania donovani antigen in urine and thereby visceral leishmaniasis. No agglutination indicates absence of antigen in urine. DAT was done with serums of all cases.Result: Among 130 clinically suspected VL cases, 70 (53.85%) cases were BM positive and 60(46.15%) cases were BM negative. All the 70 BM positive cases were positive by KAtex and DAT. Among 60 BM negative cases, 15 were positive by KAtex and 23 were positive by DAT. The sensitivity of KAtex was 100.0% and specificity was 75.0%. The sensitivity of DAT was 100.0% and specificity is 61.6%.Conclusion: In conclusion, KAtex test is a good diagnostic tool for the detection of VL in comparison with DAT.Bangladesh Journal of Infectious Diseases, June 2019;6(1):12-15